STUDI KETERAMPILAN PROSES SAINS PADA PEMBELAJARAN FISIKA MATERI GETARAN DAN - Amanah Ayu Pratama (Universitas Sriwijaya, 2014)
The objective of this study was to describe science process skills on material physics learning vibration and wave. This study used one of the descriptive designs. The sample of the study was the eighth grade students of VIII1 class of SMPN 18 Palembang. The data were obtained through observation. Based on the result of the observation that, the process of science skill used the discovery learning model that was good, especially on the problem of study, the hypothesis ofÂ the study, the design of the study, experiment, the collecting of data, the analysis of data, conclutions, and interview. The hypotheses of the study obtained the highest score, while the analysis the data of try out were the lowest score. On the other words, the students could more identify the problem that they found through the experiment than analyze the data base on the experiment that they had done.